HIV-related stigma and non-adherence to antiretroviral medications among people living with HIV in a rural setting. (August 2020) - Kalichman, Seth C.; Katner, Harold; Banas, Ellen; Hill, Marnie; Kalichman, Moira O.
Highlights: People with HIV experience cumulative stigma with effects contributing to stress. Family distancing and discrimination impact the health of people with HIV. Effects of alcohol use on medication adherence are independent of HIV-stigma. Cumulative HIV stigma impacts HIV treatment adherence through HIV-related stress.